Identifikasi Methicillin-Resistant Staphylococcus Aureus pada Tenaga Kesehatan di Instalasi Gawat Darurat dan Rawat Inap Rumah Sakit Islam Sitti Maryam Manado - Tirza M. Z. Osok; Olivia A. Waworuntu; Heriyannis Homenta (Jurnal Syntax Admiration, 2025)
Improper use of antibiotics can lead to antibiotic resistance. According to the World Health Organization (WHO), antibiotic resistance is currently one of the greatest global health threats. The 2022 WHO Global Antimicrobial Resistance and Use and Surveillance System (GLASS) report indicates that One of the common bacteria that is found to be resistant to antibiotics is Staphylococcus aureus which is resistant to methicillin or Methicillin-Resistant Staphylococcus aureus (MRSA). MRSA is recognized as a leading cause of Healthcare-Associated Infections (HAIs) and is associated with high morbidity, mortality, and healthcare costs. Research on MRSA among healthcare workers in Indonesia, especially in Manado, is still very limited, which prompted this study. Purpose: To identify the presence of MRSA among healthcare workers in the Emergency Department (ED) and inpatient wards at Sitti Maryam Islamic Hospital, Manado. Methods: A cross-sectional study involving all nurses working in the ED and inpatient wards. Nasal swab samples were cultured on MSA media and further bacterial identification was conducted. Antibiotic sensitivity testing was performed using MHA media and cefoxitin disks 30 μg. Results: Out of the 23 anterior nasal swab samples taken from healthcare workers, it was found that 13 samples (57%) of healthcare workers had Staphylococcus aureus colonization and 5 samples (38%) of them had resistance to the antibiotic cefoxitin. The overall MRSA colonization in the nasal cavities of healthcare workers was 5/23 (22%). Conclusion: MRSA was identified among healthcare workers at Sitti Maryam Islamic Hospital, Manado.